Rediscovery of Sinopla humeralis Signoret, 1864 (Hemiptera: Heteroptera: Acanthosomatidae) - Carvajal, Máriom A.; Faúndez, Eduardo I. (Zootaxa, 2013)
Sinopla humeralis Signoret, 1864 is revalidated and removed from the synonymy of Sniploa obsoletus Signoret, 1864. The first formal records from it original description and first data about its biology are provided. The type species of the genus Sinopla is discussed and the concept of the genus is expanded. The association of Sinopla humeralis with the south-ern beech Nothofagus Blume and it distribution from Maule Region to Magallanes Region in Chile, are inncluded.